Generic structure potential of rollingstone magazine cover february 9th, 2006 edition; critical multimodal discourse analysis - Kristian Dwi Putranto; Sigit Ricahyono; Rosita Ambarwati (English Teaching Journal : A Journal of English Literature, Language and Education, 2018)
Rollingstone; February 9th, 2006 edition was made because there is the meaning intended on it. The researcher uses critical multimodal discourse analysis from O’Halloran (2004), Kress and Van Leeuwen (2006), Halliday and Matthiessen (2014). The objectives of this study are to describe the generic structure potential, representational meaning, and the context of situation of Rollingstone; February 9th, 2006 edition. The approach of this study is qualitative research and the type is document research. The researcher uses document from the picture of Rollingstone; February 9th, 2006 edition which taken from Rollingstone’s official website. Analysis techniques flow model of this study are collecting the data, displaying and concluding. The results of this study are (1) There are some generic structure potential elements found. They are Lead, LoA, Comp. LoA, Display, Emblem, Announcement, Enhancer, Call and Visit Information and missing one element that is Tag. (2) The representational meaning of this magazine cover by applying narrative process for action process and conceptual representation for symbolic process. (3) The context of situation divided into field, tenor and mode. Field consists of The College Dropout Album, Jesus Walks Songs, 47th Grammy Awards, Rollingstone; February 9th, 2006 edition. Tenor consists of Kanye West as Song Writers, Rollingstone as production house and the target market. The mode consists of the word “The Passion of Kanye West”.